Efektivitas Tanaman Genjer (Limnocharis flava) Sebagai Agen Fitoremediasi Penyerapan Fosfat Pada Air Limbah Laundry Di Kota Medan - Nai Fitri Rambe, Anggi; Ivanka, Della; Olivia Anastasya Silaban, Maria; Junetti Rajagukguk, Teresia; Nilan Sari, Marlinda; Febriyossa, Adelia (Jurnal Biogenerasi, 2024)
This research aims to determine the effectiveness of the genjer plant (Limnocharis flava) in absorbing phosphate pollutants contained in laundry wastewater and to identify environmental factors that influence the effectiveness of the genjer plant (Limnocharis flava) in absorbing phosphate pollutants from laundry wastewater. The study was conducted in the Greenhouse of the Biology Department, Universitas Negeri Medan, using the constructed wetland method with variations in laundry wastewater concentrations (25%, 50%, 100%) and clean water as the control. The sample was taken from a laundry business on Jl. Tuasan, Medan City. Over 7 days of observation, parameters such as pH, temperature, turbidity, and the physical condition of the genjer plants were monitored. The results showed that genjer plants were effective in absorbing phosphate, with reduced turbidity and stabilized pH and temperature, with the 50% concentration treatment being the most optimal. This research is expected to serve as a reference for the application of phytoremediation technology using genjer plants (Limnocharis flava) as an environmentally friendly alternative for laundry wastewater treatment